PENGUKURAN OVERALL EQUIPMENT EFFECTIVENESS(OEE) UNTUK PERBAIKAN PROSES MANUFAKTUR MESIN BEAD GROMMET (Jurnal Inovisi (Teknik Industri), 2018)
AbstractThe bead grommet machine which is the object of this research is one of the machines used by companies engaged in manufacturing, especially tire manufacturing. Based on production report data shows that the achievement of the Grommet Bead Division production is the lowest compared to other divisions. So the purpose of this study is to determine the OEE (Overall Equipment Effectiveness) value and identify losses from the machine bead grommet, and analyze the causes of losses and identify priority corrective actions on the grommet bead machine based on OEE values. In this study the OEE (Overall Equipment Effectiveness) method is used to evaluate the production of bead grommet machines so that the ideal conditions of the equipment can be maintained by eliminating the six big losses. From this study, the OEE value of the ABG-5 bead grommet machine was 54.8% with losses that caused the OEE value of the ABG-5 grommet bead machine not to reach the word class value of 85%, namely the PLC Overload problem. Through brainstorming between departments, priority is given to corrective action by replacing the PLC machine bead grommet ABG-5 and making circulation for the overflow material for cooling water storage in the ABG-5 grommet bead machine. Keywords : productivity, total preventiv maintenance, TPM AbstrakMesin bead grommet yang menjadi objek penelitian inimerupakan salah satu mesin yang digunakan perusahaan yang bergerak dalam bidang manufaktur khususnya pembuatan ban.Berdasarkan data laporan produksi menunjukkan bahwa pencapaian produksi Divisi Bead Grommetmerupakan yang terendah dibandingkan dengan divisi lain.Sehinga tujuan dari penelitian ini yaitu menentukan nilai OEE (Overall Equipment Effectiveness) danmengidentifikasilosses dari mesin bead grommet, serta menganalisa penyebab losses dan mengidentifikasi prioritas tindakan perbaikan pada mesin bead grommet berdasarkan nilai OEE.Pada penelitian ini metode OEE (Overall Equipment Effectiveness)digunakan untuk mengevalusi hasil produksi dari mesin bead grommet sehingga kondisi ideal dari peralatan dapat dijaga dengan menghilangkan six big losses. Dari penelitian ini diperoleh hasil bahwa nilai OEE dari mesin bead grommet ABG-5 sebesar 54.8%denganlosses yang menyebabkan nilai OEE mesin bead grommet ABG-5 belum mencapai nilai word class sebesar 85% yaitu problem PLC Overload. Melalui brainstorming antara departement terkait diperoleh prioritas tindakan perbaikan yaitu dengan mengganti PLC mesin bead grommet ABG-5 dan membuatkan sirkulasi untuk tempat penampungan air pendingin overflow material di mesin bead grommet ABG-5. Kata kunci: produktivitas, TPM, overall equipment effectiveness